Linking the formal and informal economy : concepts and policies - Guha-Khasnobis, Basudeb; Kanbur, S. M. Ravi.; Ostrom, Elinor (Oxford ; New York : Oxford University Press, 2006)
This volume brings together a significant new collection of studies on formality and informality in developing countries. The volume is multidisciplinary in nature, with contributions from anthropologists, economists, sociologists, and political scientists. It contains contributions from among the very best analysts in development studies.
"The contributions were originally presented at a conference organized in Helsinki in September 2004 by the World Institute for Development Economics Research of the United Nations University (UNU-WIDER) in collaboration with the Expert Group on Development Issues (EGDI) at the Swedish Ministry for Foreign Affairs"--Foreword.
Includes bibliographical references and index.
oif 24/04/15
Loan
Keywords: Informal sector (Economics) -- Developing countries -- Congresses; Informal sector (Economics) -- Government policy -- Developing countries -- Congresses